Indocyanine green fluorescence to ensure perfusion in middle segment-preserving pancreatectomy: a case report - Tomohiro Iguchi; Norifumi Iseda; Kosuke Hirose; Mizuki Ninomiya; Takuya Honboh; Takashi Maeda; Fumi Sawada; Yu-ichi Tachibana; Tetsuro Akashi; Naotaka Sekiguchi; Noriaki Sadanaga; Hiroshi Matsuura (Surgical Case Reports)
Abstract Background Middle segment-preserving pancreatectomy (MSPP) is an alternative to total pancreatectomy that allows for the preservation of the endocrine and exocrine functions of the pancreas. However, maintaining perfusion to the pancreatic remnant is of critical importance. We describe the first case to our knowledge in which indocyanine green (ICG) fluorescence was used to confirm perfusion to the pancreatic remnant during MSPP. Case presentation A 79-year-old man with diabetes mellitus was referred to our hospital for treatment of a pancreatic tumor. Computed tomography revealed a hypovascular mass in the uncus of the pancreas and dilatation of the main pancreatic duct, measuring 13 mm in the tail of the pancreas. He was diagnosed with cancer of the pancreatic uncus via endoscopic ultrasound and fine-needle aspiration revealed a mixed-type intraductal papillary mucinous neoplasm (IPMN), along with high-risk stigmata in the tail of the pancreas. We performed MSPP and the length of the pancreatic remnant was 4.6 cm. The dorsal pancreatic artery was preserved and perfusion to the pancreatic remnant was confirmed by ICG fluorescence. Histopathological examination showed a pancreatic ductal adenocarcinoma in the uncus (pT1cN1M0, pStage 2B) and IPMN in the tail of the pancreas. The postoperative course was complicated by a grade B pancreatic fistula, but this was successfully treated with conservative management. The patient was transferred to a hospital 33 days after surgery. Insulin administration was necessary, but C-peptide was detectable and blood glucose was relatively well-controlled. He did not exhibit any exocrine dysfunction when pancreatic enzyme supplementation was administered. Conclusion ICG fluorescence can be used to evaluate perfusion to the pancreatic remnant during MSPP.